Metaltec - jogo de empresas voltado à qualificação de gestores de micro e pequenas indústrias - Rigodanzo, Jonas (2007)
Business games search to simulate the taking of decisions in enterprise managements also serving as a tool of learning and managemental training. In this work a game of companies based in the characteristics and typical variable of a locksmith shop was developed, that can be a tool of teach-learning and training of enterprise managers. The developed JE simulates the reality of a composed environment of six locksmith shops, being that the controlling of each company will have that to manage all its sectors, since the production until the commercialization of its products, creating and evaluating its strategies. The game was shaped mathematically, programmed in Excel language and applied a group of the PPGEP of the UFSM. The analysis of the results showed that the Metaltec, beyond being an efficient tool in the managemental qualification, also can be used as a teach-learning instrument